Micro-wineries as drivers for local economic development and innovation in lagging areas - Giuseppe Cantafio; Luana Parisi (Wine Economics and Policy, 2021)
For a long time mainstream economics has neglected the non-economic side related to economic growth. Yet, today there is increasing awareness of the role that social capital can play in spurring Local Economic Development especially in underdeveloped, remote, or lagging contexts. Microwineries represent a good example of SMEs, being small realities serving the local markets and spaces that strengthen local communities. The European Mediterranean regions have commonly been connected with these sectors. This study aims at pushing the body of knowledge in the development of microwineries in the lagging-behind contexts of Southern Europe, particularly in Southern Italy. To support the discussion, the present study will adopt a deductive approach, by analysing the San Diego wine cluster taken as a case study, since its wine market recently boomed. Findings will highlight the microwineries symbiosis with the territory itself. Useful lessons will be drawn for encouraging policymakers in undertaking actions towards strengthening the potential of microwineries and building networks among them.
Keywords: 330; Microwineries; SMEs; innovation; economic growth; business